The Effects of Integrative Reminiscence Therapy on Signs and Symptoms of Depression in the Elderly - Asghar Mohammadzadeh; Behrooz Dolatshahy; Parvaneh Mohammadkhani (Sālmand, 2011)
Objectives: The Main aim of this study was to determine the effects of integrative reminiscence therapy on signs and symptoms of depression in the institutionalized elderly.